Global Prevalence of Restless Legs Syndrome and Its Associated Factors in Pregnant Women: A Systematic Review and Meta‐Analysis - Nader Salari; Yassaman Khodayari; Roya Hassani; Fateme Gol Nazari; Masoud Mohammadi (Health Science Reports, 2026)
ABSTRACT Background and Aims Restless leg syndrome (RLS) or Willis‐Ekbom's disease is a common neurosensory motor disorder, and pregnancy is one of the secondary factors that causes it. The purpose of this systematic review and meta‐analysis study is to obtain the percentage of prevalence of restless leg syndrome during pregnancy and to analyze the available evidence about this syndrome. Methods The present study conducted the initial search in August 2022 and updated until December 2025. In this systematic review and meta‐analysis in order to find related studies, PubMed, Web of science, Science Direct, Scopus, Embase and Google scholar search engine using the keywords RLS Restless legs syndrome, Pregnancies, Pregnancy, and Gestation were searched. Random Effects Model was used to perform the analysis. Results In the review of 19 studies with a sample size of 48,231 individuals, the meta‐analysis, the prevalence of restless legs syndrome in pregnant women was reported 17% (95% CI: 11.9–23.8). In examining the factors affecting the heterogeneity of studies and examining the effect of sample size on this heterogeneity, it was reported that with increasing sample size, the global prevalence of RLS in pregnant women decreased ( p < 0.05). Conclusion Our findings reveal that the prevalence of RLS in pregnant women is 17%. Considering the factors that affect this syndrome and also the effects that this syndrome has on the lives of pregnant women, particularly the quality of sleep and psychological issues, it is recommended to address this issue as a critical public health issue.